Physiotherapeutic care to women in situation of postpartum depression: integrative review (Research, Society and Development, 2021)
This integrative literature review aimed to discuss and analyze the physical therapy care for women in a situation of postpartum depression. The research was carried out from September 15th to November 26th, 2021, in the BVS and PubMed databases, with the descriptors “physiotherapy” and “postpartum depression” with search strategies. Data were extracted through a synthesis matrix and analyzed descriptively and by typing. Seven search strategies resulted, totaling 14 eligible articles. Through the results, the definition, perspectives and potential of physical therapy care for women in a situation of postpartum depression were discussed, and the contexts, actions, activities and physical therapy resources for women in a situation of postpartum depression were discussed. This study integrated the literature and brought the analysis and discussion about physical therapy care to women's health in a situation of postpartum depression, presenting the definitions of action, contexts, actions, resources, activities, potential. Based on the above, it is concluded that the physiotherapeutic action in the care of women in a situation of postpartum depression is of fundamental importance for the care in this situation, with a range of essential action possibilities and contribution to educational, preventive, promoting perspectives. and rehabilitators to this population. Finally, it highlights the need to continue the study on this topic that addresses more specificities and intersectionality of this care.